2020
DOI: 10.1128/jcm.00794-20
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Metagenomic Next-Generation Sequencing Assay for Identifying Pathogens: a Retrospective Review of Test Utilization in a Large Children's Hospital

Abstract: Introduction: Plasma metagenomic next generation sequencing (mNGS) is a newer diagnostic method used to potentially identify multiple pathogens with a single DNA-based diagnostic test. The test is expensive, and little is understood about where it fits in the diagnostic schema. We describe our experience at Texas Children's Hospital with the mNGS assay by Karius from Redwood, CA to determine if mNGS offers additional diagnostic value when performed within one week before or after conventional testing (CT) (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 15 publications
1
36
0
Order By: Relevance
“…However, while a positive identification by mNGS can be helpful to clinicians, a negative result does not necessarily rule out infection as mNGS has missed important pathogens identified by conventional testing. 13 In our study, mNGS identified a plausible cause of infection, defined as a definite, probable or possible infection, in 49.7% of patients tested. This is comparable with a pediatric review that found 56% of mNGS results to be clinically relevant 10 but is lower than a recent prospective study that found a plausible cause of infection in 85.4% of patients with febrile neutropenia.…”
Section: Discussionmentioning
confidence: 55%
“…However, while a positive identification by mNGS can be helpful to clinicians, a negative result does not necessarily rule out infection as mNGS has missed important pathogens identified by conventional testing. 13 In our study, mNGS identified a plausible cause of infection, defined as a definite, probable or possible infection, in 49.7% of patients tested. This is comparable with a pediatric review that found 56% of mNGS results to be clinically relevant 10 but is lower than a recent prospective study that found a plausible cause of infection in 85.4% of patients with febrile neutropenia.…”
Section: Discussionmentioning
confidence: 55%
“…These viruses have poorly understood clinical signi cance. The limited clinical impact of plasma mNGS has also been reported in patients with infectious diseases [15,41]. Armstrong et al also showed that the cfDNA NGS could identify fungal pathogens and had the potential to limit excessive empiric antifungal use [42].…”
Section: Discussionmentioning
confidence: 99%
“…However, a positive plasma mNGS result for MTB complex would significantly alter a patient's management before SCT and potentially increase the chance of a good outcome post-transplant. [23][24][25] Additionally, while plasma mNGS is costly and in some cases may not add additional diagnostic information compared to conventional testing, 17 in immunocompromised patients requiring SCT, whose conventional, immune-based testing for mycobacterial infections are unavailable or unreliable, and who are receiving or have recently received broad-spectrum antimicrobial therapy or prophylaxis (impacting culture results), plasma mNGS could offer an alternative, non-invasive, rapid screening tool for infectious pathogens. Future studies should consider assessing the specificity and sensitivity of plasma mNGS in screening BCG-vaccinated immunocompromised infants for disseminated BCG infection before SCT.…”
Section: Discussionmentioning
confidence: 99%